1986
DOI: 10.3171/jns.1986.64.6.0941
|View full text |Cite
|
Sign up to set email alerts
|

Effect of vasopressin on cold-induced brain edema in cats

Abstract: Centrally released arginine vasopressin (AVP) has been implicated in the regulation of intracranial pressure (ICP) and brain water, and is elevated in the cerebrospinal fluid (CSF) of some patients with pseudotumor cerebri or subarachnoid hemorrhage. The authors have examined the relationship of AVP levels in CSF to ICP and brain water content in three experimental groups of cats with and without cold-induced vasogenic edema. With the cats under general anesthesia, a cold lesion was made and cannulas were plac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
13
0

Year Published

1989
1989
2008
2008

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(14 citation statements)
references
References 34 publications
1
13
0
Order By: Relevance
“…Our results are well in agreement with other experimental studies showing that AVP is involved in the pathophysiology of acute brain damage, for example, after subarachnoid or intracerebral hemorrhage (Doczi et al, 1984;Rosenberg et al, 1992), cortical focal lesions (Reeder et al, 1986;Bemana and Nagao, 1999), traumatic brain injury (Armstead, 2001), global cerebral ischemia (Liu et al, 1991(Liu et al, , 1996Ikeda et al, 1997), and permanent focal cerebral ischemia (Dickinson and Betz, 1992;Shuaib et al, 2002). The amount of AVP mRNA and of AVP protein increase after experimental cerebral ischemia (Liu, 1992;Liu et al, 2000) and levels of AVP are elevated in the CSF of stroke patients (Barreca et al, 2001).…”
Section: Avp During Pathologic Conditions Of the Brainsupporting
confidence: 82%
See 2 more Smart Citations
“…Our results are well in agreement with other experimental studies showing that AVP is involved in the pathophysiology of acute brain damage, for example, after subarachnoid or intracerebral hemorrhage (Doczi et al, 1984;Rosenberg et al, 1992), cortical focal lesions (Reeder et al, 1986;Bemana and Nagao, 1999), traumatic brain injury (Armstead, 2001), global cerebral ischemia (Liu et al, 1991(Liu et al, , 1996Ikeda et al, 1997), and permanent focal cerebral ischemia (Dickinson and Betz, 1992;Shuaib et al, 2002). The amount of AVP mRNA and of AVP protein increase after experimental cerebral ischemia (Liu, 1992;Liu et al, 2000) and levels of AVP are elevated in the CSF of stroke patients (Barreca et al, 2001).…”
Section: Avp During Pathologic Conditions Of the Brainsupporting
confidence: 82%
“…In the Brattleboro rat, which does not express AVP, brain sodium uptake was reduced during hypernatremia and after cerebral ischemia by 61% and 36%, respectively, and brain edema formation was reduced by 1/3 (DePasquale et al, 1989;Dickinson and Betz, 1992) while all changes were reversible when AVP was administered intracerebroventricularly (Dickinson and Betz, 1992). Most interestingly, AVP seems to influence brain edema formation after both cold injury and global cerebral ischemia, two conditions known to be associated almost exclusively with the development of vasogenic or cytotoxic brain edema, respectively (Reeder et al, 1986;Liu et al, 1996). These findings indicate that AVP may influence brain water and brain volume homeostasis by multiple pathways, for example, by influencing the permeability of the BBB and by directly modulating the cell volume of neurons and astrocytes.…”
Section: Role Of Avp For the Formation Of Brain Edemamentioning
confidence: 92%
See 1 more Smart Citation
“…Pharmacologic doses of vasopressin delivered into the CSF or brain parenchyma have been shown to induce increases in brain water in the absence of cerebral injury (D6czi et aI., 1982;Rosenberg et aI., 1988;Rosenberg et aI., 1990). Reeder et al (1986) showed that vasopressin en hanced white matter edema formation following cold-induced injury, and DePasquale et aI., (1989) showed that hypernatremia-induced brain volume regulation was attenuated in vasopressin defi ciency. In our model of partial ischemic injury, we demonstrated that vasopressin deficiency attenu ated edema formation and that intraventricular re- placement of vasopressin normalized edema forma tion.…”
Section: Discussionmentioning
confidence: 99%
“…This correlation had led to investigations concerning the role of vasopressin in brain edema formation. Although one study has demonstrated that edema formation from a cold-induced brain in jury is accelerated following intraventricular admin istration of pharmacologic doses of vasopressin (Reeder et al, 1986), it is not known whether re lease of endogenous vasopressin accelerates edema formation.…”
mentioning
confidence: 99%